Role of Osteopontin in Right Ventricular Remodeling - Mamazhakypov, Argen; Justus Liebig University Giessen (My University, 2019)
Background: Right ventricular (RV) failure determines the survival and outcome of patients with pulmonary hypertension (PH) with different etiologies. Circulating osteopontin (OPN) levels are elevated in patients with PH and correlate with RV dysfunction in those patients. We, therefore, hypothesized that OPN deficient mice are protected from deleterious RV remodeling and the reconstitution of OPN with chronic administration of recombinant OPN (rOPN) in those mice abolish the effects of OPN deficiency on the RV in a mouse model of RV failure. Methods: We performed sham or pulmonary artery banding (PAB) surgery in OPN deficient (OPN KO) and wildtype (WT) mice and treated them with rOPN for 3 weeks. Results: PAB surgery caused a severe increase in RV systolic pressure and RV remodeling and dysfunction in both OPN KO and WT mice as shown by invasive hemodynamic and echocardiographic measurements. rOPN treatment had no effects on the parameters of RV remodeling and dysfunction in both OPN KO and WT mice. Despite similar degrees of RV remodeling, PAB-operated OPN KO mice displayed increased mortality, however, treatment with rOPN improved survival of those mice. Conclusions: Lack of OPN led to the increased mortality of mice with RV failure indicating the crucial role of OPN in this condition. In addition, improved survival of OPN KO mice with rOPN treatment suggests the therapeutic potential of OPN for the treatment of RV failure.
Keywords: osteopontin; right ventricle; pulmonary artery banding; ddc:570